Computational biomechanics in cross-country skiing - Holmberg, J. L. (Linköpings Studies in Science and Technology; 1346, 2008)
Traditionally, research on cross-country skiing biomechanics is based mainly on experimental testing alone. Trying a different approach, this thesis explores the possibilities of using computational musculoskeletal biomechanics for cross-country skiing. As far as the author knows, this has not been done before.